Evaluasi Kinerja Turboexpander (KE -5601) Berdasarkan Kondisi Minimum Feed Di Unit 56 LPG Plant PT Perta Arun Gas - Zuraihan, Zuraihan; Ridwan, Ridwan; Suryani, Suryani (Jurnal Riset, Inovasi, Teknologi & Terapan, 2023)
A turboexpander is an escrow and compressor connected in a process. The turboexpander rotates at high speed by utilizing gas expansion in the expander and gas compression in the compressor. The compressor-expander consists of wheels at each end that are gassed. The gas flow at high speed will rotate the shaft connected to the end of the compressor part. The purpose of this paper is to calculate the efficiency of equipment that is able to maximize the separation process between methane and ethane, and simulate flow and pressure variations to see changes in efficiency. The method used is to take the measured output value from the tool in the form of flow rate, pressure and temperature. Based on the calculation results obtained η=77%, HpExpander=2619.40 Horsepower, shaft speed=5220.76 rpm, and QLoss=22%.